The effects of distribution channel innovation and efficiency on Indonesian small and medium enterprise’s performance - Kuswantoro , F.; Mohd Rosli, M.; Abdul Kader, R. (2012)
It has been debated at length that SMEs are crucial for generating employment, reducing poverty, adding value and contributing to Gross Domestic Product. As businesses are more exposed to the globalised world, promotion strategy, without proper innovation in distribution channel, is insufficient for SMEs to enhance their performance. Unfortunately, studies on the relationship between distribution channel innovation and firm performance, especially among export-oriented SMEs are hardly found. As such, this study attempts to examine how distribution channel innovation affects Indonesian SMEs. Using the regression analysis on 126 samples collected from agricultural-based, export-oriented SMEs in the Special Province of Yogyakarta and the surrounding areas, this study found that innovation in distribution channel was positively associated with distribution channel efficiency, which in turn positively enhanced the SME performance. This finding indicates that innovation in distribution channel should improve the efficiency of distribution channel without which firm performance would not be enhanced. This could be a great challenge for SMEs to manage their innovation in distribution channel activities.